Healthcare professionals' perceived barriers and facilitators of health behavior support provision: A qualitative study. (17th November 2022) - Bouwman, Eline; Pluijm, Saskia M. F.; Stollman, Iridi; Araujo‐Soares, Vera; Blijlevens, Nicole M. A.; Follin, Cecilia; Falck Winther, Jeanette; Hjorth, Lars; Kepak, Tomas; Kepakova, Katerina; Kremer, Leontien C. M.; Muraca, Monica; et al.
Abstract: Background: Childhood cancer survivors (CCSs) have an increased risk of developing chronic health conditions. Evidence suggests that poor health behaviors further increase health risks. Healthcare professionals (HCPs) involved in survivorship care have a key role in providing health behavior support (HBS) but can feel limited in their ability to do so. This study aims to explore European HCPs perceived facilitators and barriers to providing HBS to CCSs. Methods: Five focus groups with 30 HCPs from survivorship care clinics across Europe were conducted. Topic guides were informed by the Theoretical Domains Framework (TDF) to capture domains that may influence provision of HBS. Focus groups were analyzed with thematic analysis. Transcripts were inductively coded, after which axial coding was applied to organize codes into categories. Finally, categories were mapped onto the TDF domains. Results: Nine TDF domains were identified in the data. The most commonly reported TDF domains were "Knowledge", "Skills", and "Environmental context and resources". HCPs indicated that their lack of knowledge of the association between late effects and health behaviors, besides time restrictions, were barriers to HBS. Facilitators for HBS included possession of skills needed to pass on health behavior information, good clinic organization, and an established network of HCPs. Conclusions: This study identified education and training of HCPs as key opportunities to improve HBS. Survivorship care clinics should work towards establishing well‐integrated structured care with internal and external networks including HBS being part of routine care. Proper understanding of facilitators and barriers should lead to better survivorship care for CCSs. Abstract : Healthcare Professionals' Perceived Barriers and Facilitators of Health Behavior Support Provision: a qualitative study.